Pengaruh Program Pemutihan Denda Pajak Kendaraan Bermotor, Pembebasan Bea Balik Nama Kendaraan Bermotor, Kualitas Pelayanan dan Sosialisasi Perpajakan terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor pada UPT.SAMSAT Medan Utara - Silviani, Echa; Ina liswanty (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Taxpayer Compliance is a condition when taxpayers fulfill their tax obligations and tax rights correctly and precisely based on the applicable taxation law. This research aims to determine Motor Vehicle Tax Reduction, Exemption of Transfer of Title Fees, Service Quality and Tax Socialization of Motor Vehicle Taxpayer Compliance with UPT. North Medan Samsat. This type of research is quantitative research using survey methods. The sampling technique used was simple random sampling with a population of 479,555 Motor Vehicle Taxpayers and a sample of 100 respondents. The data analysis techniques used in this research were descriptive statistical tests, classical assumption tests and multiple linear regression analysis using the IBM SPSS Version 25.0 program. The results of this research show that the variables: Motor Vehicle Tax Reduction, Transfer of Title Fee Exemption, Service Quality and Tax Socialization simultaneously simultaneously influence Motor Vehicle Taxpayer Compliance.